GREENHOUSE SOLAL DRYER WITH LPG GAS BURNER FOR DRYING BANANAS - Piwsaoad, Jagrapan (Life Sciences and Environment Journal, 2023)
This work presents the experimental performance of a greenhouse solar dryer for drying bananas. The dryer consists of a polycarbonate sheet covered on a concrete floor. The dryer is 9 m in width, 24 m in length and 4 m in height. Nine 15-W DC fans powered by two 50-W PV modules were used to ventilate the dryer. Use an LPG gas burner to increase the temperature. For performance investigation, the dryer was used to dry ten batches of bananas. For each batch, 1,000 kilograms of bananas were dried in the dryer. Results obtained from the experiments showed that drying temperatures varied from 27๐C to 55๐C. In addition, the drying time for drying bananas was 5 days, compared to the 10 days required for natural sun drying. Bananas dried in the dryer were completely protected from rain and high-quality bananas were obtained.